Analysis of the Impact Of The Profitability Ratios on Corporate Zakat Expenditure (Study on Islamic Commercial Banks in Indonesia from 2020 to 2023) - Agustiani, Nely; Hasanah, Shofia Mauizotun (IQTISHADUNA, 2024)
This research aims to determine the effect of profitability ratios on corporate zakat expenditure in Islamic commercial banks in Indonesia from 2020 to 2023. This quantitative research utilizes secondary data. The dependent variable in this study is corporate zakat, and the independent variables are profitability ratios proxied by Return on Assets (ROA) and Return on Equity (ROE). The data analysis method uses panel data regression. The population in this study consists of Islamic commercial banks in Indonesia registered with the Financial Services Authority. The sampling technique used is purposive sampling, resulting in a sample of 8 Islamic commercial banks. Data processing in this study uses the statistical data analysis tool Eviews version 10. The results of the study can be concluded partially that the Return on Assets variable has a significant negative effect on corporate zakat expenditure, and the Return on Equity variable has a significant positive effect on corporate zakat expenditure. Simultaneously, it also shows that Return on Assets and Return on Equity affect corporate zakat.